O trabalho do policial militar de São Luís - MA: um olhar da Psicodinâmica do Trabalho - PINHO, Higor Ribeiro (2018)
This study aimed to analyze the repercussions of the work on the subjectivity of military police officers in the administrative sector. To that end, we sought to identify the experiences of pleasure and suffering, as well as the coping strategies developed by them in the face of adverse situations in the work context. For the theoretical reference of the Psychodynamics of Work, the work can be constituted as source of pleasure and suffering. Data collection consisted of documental and bibliographical research, as well as semi-structured interviews with six policemen, three men and three women. The data collected were analyzed using the Bardin content analysis. The results point to a work marked by overwork and lack of autonomy in the face of rigid organization. The sources of pleasure signaled by the police officers are the sense of importance of the work they perform, the friendship established between them and the salary. However, this worker is embedded in a work environment that does not offer many resources for transformation into a healthy environment. In this sense, they stand out as sources of suffering, hierarchical rigidity, lack of recognition, loss of friends, difficulties for promotion and overwork. Faced with the predominance of suffering experiences, the police use from justifications for this suffering, to passive behavior and banalization of situations.